2023
DOI: 10.2147/jhc.s420828
|View full text |Cite
|
Sign up to set email alerts
|

Resection Margin Width Does Not Influence the Prognosis of Solitary Hepatocellular Carcinoma After Anatomic Resection: A Real-World Study from China

Abstract: Purpose The influence of resection margin (RM) width on the prognosis of solitary hepatocellular carcinoma (HCC) following anatomical resection (AR) has yet to be determined. Therefore, we conducted a real-world study to identify the optimal RM width and assess its impact on the outcomes of solitary HCC patients undergoing AR. Methods The data pertaining to patients diagnosed with solitary HCC who underwent AR between December 2012 and December 2015 were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have found that many microsatellite foci are present around liver tumors after radical ablation therapy. Furthermore, 19% of satellite nodules in HCC nodules with diameters of 3 cm or less could not be identified before treatment ( 13 ), and approximately 20% of the microsatellite foci were located beyond 1.0 cm from the edge of the HCC lesion ( 14 ). The conventional ablation zone typically extends approximately 0.5–1.0 cm beyond the tumor margin ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that many microsatellite foci are present around liver tumors after radical ablation therapy. Furthermore, 19% of satellite nodules in HCC nodules with diameters of 3 cm or less could not be identified before treatment ( 13 ), and approximately 20% of the microsatellite foci were located beyond 1.0 cm from the edge of the HCC lesion ( 14 ). The conventional ablation zone typically extends approximately 0.5–1.0 cm beyond the tumor margin ( 15 ).…”
Section: Discussionmentioning
confidence: 99%